Bloodlines : recovering Hitler's Nuremberg Laws, from Patton's trophy to public memorial /: recovering Hitler's Nuremberg Laws, from Patton's trophy to public memorial. ([2016]) - Platt, Tony, 1942-; O'Leary, Cecilia Elizabeth, 1949-
No abstract available